REFLEKSI KRITIS ATAS METODE BERFILSAFAT DAMARDJATI SUPADJAR - Santoso, Heri (Jurnal Filsafat "WISDOM", 2007)
The strength-ness of Damardjati Supadjar philosophical thought method is: unique, operational, and testified. Unique consist in that his thought are special and different from the other philosophers. The meaning of operational is applicable by one who ready to experience it. Testable has a meaning that someone who doing with the method, necessarily acknowledge that the method effective enough to developing the new consciousness. The weakness of the method are: style of the forwarding of ideas which sometime too vulgar (look-likes porno) and to the indigent beginner difficult to catch the substance of ideas, so that they impress the ideas less systematic. The contribution of Damardjati Supadjar method for the developing of philosophy, specially for Indonesian philosophy is to be able to offer the pattern of typical patterned thinking and attitude, representing result of cultural local genius of Java, Nusantara, Islam, And world culture.